Study of applications of a modernized sprinkler irrigation system - Mohd. Hudzari, Haji Razali; Syazili, Roslan; Nur Sakinah, Mohamad (2013)
This study introduced the application of sprinkler in irrigation for farm mechanization practical. Sprinkler Irrigation is a method of applying irrigation water which is similar to rainfall. Water is distributed through a system of pipes usually by pumping. It is then sprayed into the air and irrigated entire soil surface through spray heads so that it breaks up into small water drops which fall to the ground. It provide efficient coverage for small to large areas and are suitable for use on all types of properties and also adaptable to nearly all irrigable soils since sprinklers are available in a wide range of discharge capacity. With careful calculation and selection showed in this paper through nozzle sizes, operating pressure and sprinkler spacing the amount of irrigation water required to refill the crop root zone can be applied nearly uniform at the rate to suit the infiltration rate of soil.